2008
DOI: 10.1093/rpd/ncn051
|View full text |Cite
|
Sign up to set email alerts
|

Accidental gamma dose measurement using commercial glasses

Abstract: Commercial glasses have been investigated for their application in accidental gamma dose measurement using Thermoluminescent (TL) techniques. Some of the glasses have been found to be sensitive enough that they can be used as TL dating material in radiological accident situation for gamma dosimetry with lower detection limit 1 Gy (the dose significant for the onset of deterministic biological effects). The glasses behave linearly in the dose range 1-25 Gy with measurement uncertainty +/- 10%. The errors in acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Many studies have been led by means of several techniques in order to investigate the possibility of using different types of glasses as dosimetric materials [1][2][3][4][5]. In particular, thermoluminescence (TL) studies on commercial glass samples have revealed their potential use as TL dosimeters for accidental gamma dose [6,7]. Moreover, TL investigations on watch glasses [7,8] have shown some of their dosimetric properties for gamma radiation beams.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been led by means of several techniques in order to investigate the possibility of using different types of glasses as dosimetric materials [1][2][3][4][5]. In particular, thermoluminescence (TL) studies on commercial glass samples have revealed their potential use as TL dosimeters for accidental gamma dose [6,7]. Moreover, TL investigations on watch glasses [7,8] have shown some of their dosimetric properties for gamma radiation beams.…”
Section: Introductionmentioning
confidence: 99%
“…Glasses: Following studies of EPR from smartphone and watch glass, several research groups have examined the TL signals from these same materials, building on earlier work demonstrating that glass in general can be used as an accident dosimeter using TL (e.g., Narayan et al, 2008). Thus, Bassinet et al (2010a) compared the TL and EPR signals from both watch glass and glass from various touch-screen phones.…”
Section: Electronic Componentsmentioning
confidence: 99%
“…The radiation induced effects in the irradiated glass can be indeed employed for dose evaluation, by means of two physical techniques, i.e. thermoluminescence (TL) (Teixeira et al, 2008;Narayan et al, 2008) and electron spin resonance (ESR) (Gancheva et al, 2006;Teixeira et al, 2005).…”
Section: Introductionmentioning
confidence: 99%